Obtaining and Characterisation of Starch-Based Edible Films Incorporating Honey, Propolis and Bee Bread - Mironescu Monica (Acta Universitatis Cibiniensis. Series E: Food Technology, 2019)
This research investigates the physical-chemical, sensorial and mechanical characteristics of starch-based edible films incorporating three types of bee hive products: honey, propolis and bee bread, in concentrations varying from 1% to 3%, reported to starch. The results indicates an increasing of films moisture, water activity, ash content and acidity, in the order: honey<propolis<bee bread, all values increasing with the increasing of hive products percentage into the control film; aw is remaining at very low values, under 0.4. Sensorial analysis indicated honey as the better suited for improving taste and flavour and bee bread for increasing colour intensity of the films; the sensorial characteristics are maintained during 30 days of films storage, in all cases. Compared with the control starch-based film (which is elastic, brittle and hard), the films containing 2% bee hive products are elasto-plastic and more resistant to penetration, the resistance increasing in the order: bee bread<propolis<honey.